Physiological and Pharmaceutical Considerations for Rectal Drug Formulations - Hua, Susan (Frontiers in Pharmacology, 2019)
Although the oral route is the most convenient route for drug administration, there a number of circumstances where this is not possible from either a clinical or pharmaceutical perspective. In these cases, the rectal route may represent a practical alternative and can be used to administer drugs for both local and systemic action. The environment in the rectum is considered relatively constant and stable and has low enzymatic activity in comparison to other sections of the gastrointestinal tract. In addition, drugs can partially bypass the liver following systemic absorption, which reduces the hepatic first-pass effect. Therefore, rectal drug delivery can provide significant local and systemic levels for various drugs, despite the relatively small surface area of the rectal mucosa. Further development and optimization of rectal drug formulations have led to improvements in drug bioavailability, formulation retention, and drug release kinetics. However, despite the pharmaceutical advances in rectal drug delivery, very few of them have translated to the clinical phase. This review will address the physiological and pharmaceutical considerations influencing rectal drug delivery as well as the conventional and novel drug delivery approaches. The translational challenges and development aspects of novel formulations will also be discussed.